Understanding the West African Monsoon from the analysis of diabatic heating distributions as simulated by climate models. (30th January 2017) - Martin, G. M.; Peyrillé, P.; Roehrig, R.; Rio, C.; Caian, M.; Bellon, G.; Codron, F.; Lafore, J.‐P.; Poan, D. E.; Idelkadi, A.
Abstract: Vertical and horizontal distributions of diabatic heating in the West African monsoon (WAM) region as simulated by four model families are analyzed in order to assess the physical processes that affect the WAM circulation. For each model family, atmosphere‐only runs of their CMIP5 configurations are compared with more recent configurations which are on the development path toward CMIP6. The various configurations of these models exhibit significant differences in their heating/moistening profiles, related to the different representation of physical processes such as boundary layer mixing, convection, large‐scale condensation and radiative heating/cooling. There are also significant differences in the models' simulation of WAM rainfall patterns and circulations. The weaker the radiative cooling in the Saharan region, the larger the ascent in the rainband and the more intense the monsoon flow, while the latitude of the rainband is related to heating in the Gulf of Guinea region and on the northern side of the Saharan heat low. Overall, this work illustrates the difficulty experienced by current climate models in representing the characteristics of monsoon systems, but also that we can still use them to understand the interactions between local subgrid physical processes and the WAM circulation. Moreover, our conclusions regarding the relationship between errors in the large‐scale circulation of the WAM and the structure of the heating by small‐scale processes will motivate future studies and model development. Key Points: Diabatic components in the West African Monsoon (WAM) region are available from four model families with different physical packages Analysis of these diabatic components gives insight into the processes influencing the WAM and indicates where model development is needed Radiative heating in the Sahara and the representation of clouds and convection in the rainband and Sahel are key for the WAM circulation